The Managerial Influence of The Principal on Improving The Performance of Elementary School Teachers In Cluster 2 Plampang District - Ardiansyah, Ahyar; Umar, Umar; W, Yunanri (Empiricism Journal, 2022)
The background of this research is related to the low performance of elementary school teachers in Cluster 2, Plampang District. The main problem is the ability of the principal's managerial skills in carrying out his functions.  The purpose of this study is to determine the effect of the principal's managerial application on teacher performance. This research was conducted using a non-experimental quantitative approach. The population and sample in this study were 62 people. The instrument used in this study was to use a closed questionnaire with answer choices on a likert scale of 4, which means that respondents can only choose one answer. The data analysis techniques in this study are descriptive analysis and simple regression analysis. The result showed: (1) the principal's managerial implementation process towards improving teacher’s performance has gone well, (2) there is a managerial correlation of the principal to teacher’s performance, as evidenced by the results of the counting test of 9,151 > ttabel 1.66. The correlation of the principal's managerial influence on teacher’s performance was 0.687 in the strong category. The magnitude of the effect of the principal's managerial effectiveness on teacher’s performance was 58.3%, (3) there is an influence of the principal's managerial effectiveness on teacher’s performance, as evidenced by the results of the paired sample t-test showing that the significance amounts to 0.000 < 0.05, so there is a noticeable or significant difference between the principal's managerial influence on teacher performance. The research advice is for the headmaster to continuously improve his managerial skills, and for teachers it is advisable to always improve his performance.